A Study of Muscular Objective Tinnitus Caused by the Eustachian Tube - Mizuta, Kunihiro; Endo, Shiori; Arai, Maki (International Journal of Practical Otolaryngology, 2022)
Objective tinnitus that originates in muscles can be heard by others as well as by the patient. Although there have been many reports of objective tinnitus, each report has been limited to a small number of cases that have varied from one another, with some being accompanied by such findings as voluntary and/or involuntary movement of the soft palate and eardrum, as well by blinking, and the etiology has remained unclear. We analyzed 16 cases of objective tinnitus synchronous with the opening and closing of the eustachian tube. The voluntary and involuntary movements of the soft palate and eardrum were consistent with the findings in previous reports. The 16 cases included 11 cases of patulous eustachian tube and in 10 of them the patient voluntary induced tinnitus to prevent the symptoms of a patulous eustachian tube. These patients created an opportunity to close the patulous eustachian tube by repeating opening and closing. The sound of the opening and closing of the eustachian tube became an objective tinnitus. The tinnitus was heard only voluntary in seven cases and voluntary and involuntarily in nine cases; one of patients was tentatively diagnosed with middle ear myoclonus and another was diagnosed with pharyngolaryngeal myoclonus. Patulous eustachian tube was first described as one of the causes of objective tinnitus. We speculated that the soft palate and eardrum movements were initially voluntary, but that some of them became involuntarily. If this involuntary movement is seen at the time of examination, it may be diagnosed as myoclonus. Psychological factors may be involved in the transitions from voluntary to involuntary, but further research will be necessary to assess this possibility.
Keywords: patulous eustachian tube; middle ear myoclonus; palatal myoclonus